A Micro Cogeneration System with LNG Cold Utilization-part 1: Energetic, Economic and Environmental Analyses. (May 2017) - Kanbur, Baris Burak; Xiang, Liming; Dubey, Swapnil; Choo, Fook Hoong; Duan, Fei
Abstract: Few studies have been studied on the LNG cold utilization with micro-cogeneration systems while many studies were related to large scale power generation systems. This study proposes a combined LNG cold utilized micro-cogeneration system which includes an LNG pump, an LNG vaporizer, a combustion chamber, a recuperator, a compressor, a gas turbine and a heat exchanger. Economic, energetic and environmental analyses are conducted according to various ambient air temperatures and the results are compared with overall performance of the conventional micro c-generation system. The generated electricity rate and the thermal efficiency are found the same for both investigated cycles. However, the payback period is approximately 6% higher than the conventional cycle. The mean environmental payback period was found approximately 4.8 years.